Analisis Kinerja Keuangan Daerah Kota Madiun Tahun 2024 - Purwaningsih, Endry; Deamarsya, Elfreda; Rahadiantino, Lienggar (Indonesian Journal of Development Studies, 2025)
This study aims to evaluate the financial performance of the Government of Madiun City in the 2024 fiscal year using a quantitative descriptive approach. The analysis focuses on key fiscal indicators including local revenue (PAD) effectiveness, financial independence, spending efficiency, liquidity, solvency, and the Debt Service Coverage Ratio (DSCR). Data were obtained from the 2024 audited financial statements, including the Budget Realization Report, Balance Sheet, and Cash Flow Statement. The results indicate that Madiun City achieved a PAD effectiveness rate of 99.63% and a financial independence ratio of 31.25%, suggesting a moderately independent fiscal stance. Spending efficiency was recorded at 93.57%, demonstrating strong alignment between budget planning and implementation. A DSCR of 27.44x highlights a robust debt-servicing capacity. Additionally, liquidity and solvency ratios point to stable short- and long-term fiscal conditions. However, the relatively low expenditure growth and continued reliance on central government transfers emphasize the need to strengthen local revenue strategies. The study concludes that while Madiun City exhibits sound fiscal management, there remains potential for improving financial autonomy and optimizing strategic investment.